STRENGTHENING ENVIRONMENTALLY CARING CHARACTER THROUGH LEARNING AT SCHOOL - Rintoni Rintoni; Kama Abdul Hakam; Suroso Adi Yudianto; Warlim Warlim (Jurnal Cakrawala Pendas, 2025)
The main problem of the environment is human attitudes and behavior that are not friendly to the environment. This shows the weakness of character building in the education process. This research aims to portray the method of value cultivation carried out by teachers to strengthen students' environmental care character in ecology learning at school on the theme of ecosystem balance. This study discusses strategies for improving students' environmental care character in one of the elementary schools in Subang Regency, West Java province with  subjects of the research were elementary school teachers and sixth grade elementary school students.. The approach used in this research is a qualitative approach with a case study research method and analyzed using thematic analysis techniques. The data collection process was carried out through stages of observation, interviews, and discussions involving 21 respondents consisting of principals, teachers and students. The results of the research show that the method used by teachers to strengthen students' environmentally caring character in ecological learning is through 5 (five) methods: 1) Information transfer, 2) Training, 3) Habituation, 4) Modeling, and 5) Conditioning. The need for teachers to apply creative and innovative strategies to strengthen students' character in classroom learning, whether in the form of methods, media, approaches and others in learning. Furthermore, other research needs to be carried out in other learning areas to strengthen students' environmentally caring character at school, it can even be developed in school culture and extracurricular activities at school.